Primary adrenal insufficiency secondary to ileocecal tuberculosis - Kumar, Adesh; Pal, Debasmita; Ojha, Aditya (International Journal of Research in Medical Sciences, 2026)
Ileocecal tuberculosis, the most common form of gastrointestinal tuberculosis, is usually caused by Mycobacterium tuberculosis, which is also the leading infectious cause of adrenalitis. Adrenal involvement can result in primary adrenal insufficiency, presenting with weakness, fatigue, hypotension, electrolyte imbalance, and hyperpigmentation. We present the case of a 43-year-old male with recurrent vomiting, fatigue, orthostatic dizziness, and generalized hyperpigmentation. His blood pressure was 100/80 mmHg, and laboratory tests showed low serum cortisol, elevated ACTH, hyponatremia, and hyperkalemia—findings consistent with primary adrenal insufficiency. Imaging revealed bilateral adrenal enlargement, a thickened ileocecal junction, and enlarged mesenteric lymph nodes. Colonoscopy demonstrated a terminal ileal stricture with granulomatous inflammation, and adrenal biopsy showed caseous necrosis. GeneXpert confirmed rifampicin-sensitive M. tuberculosis, indicating disseminated tuberculosis originating from the ileocecal region. The patient was started on standard anti-tubercular therapy with corticosteroid replacement for Addison’s disease. This case report highlights disseminated tuberculosis presenting as primary adrenal insufficiency secondary to ileocecal tuberculosis, an uncommon yet clinically significant association. Adrenal tuberculosis should be suspected with hyperpigmentation, electrolyte imbalance, and bilateral adrenal lesions; early diagnosis enables therapy, preventing adrenal crisis.